The Role of Corporate Social Responsibility in Improving the Quality of Social Life and Environmental Sustainability and its Implications for National Political Dynamics - Suhadi Sukendar Situmorang; Abdullah Sulaiman (Jurnal Multidisiplin Indonesia, 2025)
Corporate Social Responsibility (CSR) is a company's commitment to implementing business practices that are not only profit-oriented but also social and environmental aspects. This study aims to analyze the role of CSR in improving the quality of social life in the community and its contribution to environmental sustainability. In addition, this study also highlights how the implementation of CSR can influence national political dynamics, both through improving the company's image in the public eye and through pressure on policymakers to be more responsive to sustainability issues. Well-integrated CSR can create harmonious relationships between companies, communities, and governments. The implementation of CSR that focuses on education, health, local economic empowerment, and environmental preservation has been proven to improve social welfare and minimize the negative impacts of industrial activities on the environment. On the other hand, CSR activities also have political potential because they can shape public opinion, influence policy direction, and even be used as a tool for corporate diplomacy. Thus, CSR is not only an ethical instrument in the business world but also has a strategic impact on the social and political order at the national level. This study recommends a more holistic and sustainable CSR approach so that its benefits can be widely felt by all stakeholders.